On Lyapunov functionals for linear functional difference equations - Melchor-Aguilar, D. (Systems & control letters, 2019)
This paper presents new Lyapunov results for investigating the exponential stability property of general classes of linear functional difference equations by means of continuous and differentiable functionals. The results generalize some existing ones for the exponential stability of difference equations in continuous time with discrete and discrete plus distributed delays.